Faktor-Faktor Yang Mempengaruhi Minat dan Perilaku Penggunaan Sistem E-Filing Di Kota Denpasar dengan Model UTAUT - Komala Dewi, Ni Kadek Lisa Rosita; Yadnyana, I Ketut (E-Jurnal Akuntansi; Vol 21 No 3 (2017), 2017)
Directorate General of Taxation began to modernize the tax system in 2002. One result of the modernization is e-Filing, e-Filingissued by the tax authorities in order to facilitate reporting of the annual tax return the taxpayer and tax administration Indonesia. The purpose of this study was to to determine the factors that affect the interests and behavior of the use of e-Filing system by applying the model Unified Theory of Acceptance and Use of Technology (UTAUT). This study took place in the city of Denpasar. This study uses a formula Slovin. Samples are taken about 100 people e-Filing users, with a sampling method that is accidental sampling. Data was collected by distributing questionnaires. Mechanical analysis using multiple linear regression analysis. The results showed that the variables of performance expectancy, effort expectancy, social influence positive effect on the interest in the use of e-Filing system . Keywords: UTAUT, Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, Interests Usage and Behavior of Use